Kinetics of the volatilization removal of mercury from mercury sludge by microwave heating. (24th August 2018) - Liu, Jian; Yang, Kun; Zhang, Libo; Liu, Chenhui; Liu, Chao; Lin, Guo
Abstract: The problems associated with mercury contamination of the environment have received increasing attention. In this work, the unreacted-core model for volatilization of mercury sludge (MS) generated from lead and zinc smelting processes were carried out. The species of mercury on the surface of MS was studied. The results showed that the Mercury species (except HgS) was found to be structurally stable during the volatilization process, which was further verified by thermogravimetry (TG), and x-ray-photoelectron spectrograph (XPS) analyses. The volatilization rate was approximately 99.8% for HgS at 45 min under 873 K. The volatilization of HgS from MS was found to be controlled by gas–solid diffusion with activation energy of 82.16 kJ mol −1 (19.64 kcal mol −1 ).